Adenosquamous carcinoma of the ampulla of Vater – an unusual neoplasia with poor prognosis - Revoredo Rego, Fernando (2014)
Adenosquamous carcinoma of the ampulla of Vater is a rare neoplasia (1% of incidence of all ampulla of Vater´s neoplasias), in which both glandular and squamous elements are histologically malignant. In this study, we report the case of a 61 years old woman who presented jaundice and abdominal pain. The patient was diagnosed with adenocarcinoma of the ampulla of Vater and underwent pancreaticoduodenectomy. A R0 (no residual disease by microscopy) resection was performed. The final diagnosis was adenosquamous carcinoma of the ampulla of Vater, T4N0Mx. Two and one half months later she had multiple liver metastases and died 3 months after surgery. An updated review of this unusual disease and of its dismal prognosis is made.